2000
DOI: 10.1029/1999gl010939
|View full text |Cite
|
Sign up to set email alerts
|

Climate implications of GWP‐based reductions in greenhouse gas emissions

Abstract: Abstract. Possible implications of a GWP-based implementation of GHG reductions on future man-made climate change are explored. Abatement scenarios are established in terms of "COx equivalents" using GWP100; one scenario reducing COx only, and one reducing short-lived gases, mainly CH4. Future temperature changes are calculated by using a simple climate model. Equal emission scenarios in terms of COx equivalents do not imply equivalent climate responses and large differences in the magnitude and rate of temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
67
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 6 publications
1
67
0
1
Order By: Relevance
“…It has been suggested that an additional short-term (Fuglestvedt et al 2000;Rypdal et al 2005;Jackson 2009) or mid-term target (O'Neill et al 2010) can be introduced to the climate policy as an interim goal leading toward the long-term target. The motivation to set up such an interim target may also be as a means to avoid crossing the tipping elements (Lenton et al 2008) or to curb environmental side-effects (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that an additional short-term (Fuglestvedt et al 2000;Rypdal et al 2005;Jackson 2009) or mid-term target (O'Neill et al 2010) can be introduced to the climate policy as an interim goal leading toward the long-term target. The motivation to set up such an interim target may also be as a means to avoid crossing the tipping elements (Lenton et al 2008) or to curb environmental side-effects (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The scientific critique has pointed to the choice of indicator (i.e. radiative forcing rather than temperature response), the fact that a constant background atmosphere is used (thereby overlooking feedbacks on lifetime and radiative forcing of the gases), the use of an impulse emission rather than a sustained or finite step emission change, and that equal emissions, weighted by GWP, can give very different climate impacts, depending on the mix of gases 2 (Smith, 2003;O'Neill, 2000;Smith and Wigley, 2000a,b;Fuglestvedt et al, 2000;Reilly et al, 1999).…”
mentioning
confidence: 99%
“…There is a delicate balance between metrics that adequately include our understanding of the relevant climateimpact parameters (e.g., sea-level rise, ecosystem change, economic consequences, etc.) and those with a level of scientific uncertainty and controversy low enough to be perceived as acceptable by policy makers; this may be one reason the GWP, despite its shortcomings (4,23,24), has retained favor in terms of its use in the Kyoto Protocol (18).…”
Section: Difficulties In Defining a Gwp For No Xmentioning
confidence: 99%